Au-Coated Ni80Fe20 Submicron Magnetic Nanodisks: Interactions With Tumor Cells - Divieto, Carla; Barrera, Gabriele; Celegato, Federica; D'Agostino, Giancarlo; Di Luzio, Marco; Coïsson, Marco; Lapini, Andrea; Mortati, Leonardo; Zucco, Massimo; Pavarelli, Stefano; Sassi, Maria P.; Tiberto, Paola (Frontiers in Nanotechnology, 2020)
Effective interaction and accumulation of nanoparticles (NPs) within tumour cells is crucial for NP-assisted diagnostic and therapeutic biomedical applications. In this context, the shape and size features of NPs can severely influence the strength of adhesion between NPs and cell and the NPs internalization mechanisms. This study proved the ability of the PT45 and A549 tumor cells to uptake and retain magnetic Au-coated Ni80Fe20 nanodisks (NDs) prepared by means of a bottom-up self-assembling nanolithography technique assisted by polystyrene nanospheres. The chosen geometrical parameters, i.e. diameter (≈ 650 nm) and thickness (≈ 30 nm), give rise to magnetic domain patterns arranged in vortex state at the magnetic remanence. PT45 and A549 cell lines were cultured in presence of different concentrations of Au-coated Ni80Fe20 nanodisks (NDs) and NDs biocompatibility was evaluated by viability and proliferation tests. Electron microscopy techniques and a combined CARS (Coherent Anti-Stokes Raman Scattering) and TPL (two-photon photoluminescence) microscopy allow to localized and distinguish the NDs within or attached to the tumor cells without any labeling. A quantitative measurement of NDs amount retained within tumor cells as a function of NDs concentrations was performed by Instrumental Neutron Activation Analysis (INAA) characterization technique.